Bermuda Triangle - Zuchora-Walske, Christine; Chamberlin, W. Sean (Minneapolis, MN : ABDO Pub. Co., 2012)
Discusses the mysterious disappearances within and the cultural impact of the Bermuda Triangle.
Flight 19 -- A watery grave -- Looking back on Flight 19 -- Weaving a web of mystery -- Blame it on aliens -- Some facts are hard to ignore -- A mystery solved? -- The Bermuda Triangle today.
99472
Keywords: Bermuda Triangle